Discursive Islam and Maritime Tradition: The Islamization of the Maccera Tasi Ritual in Luwu, South Sulawesi - Al Mudzill, Al Mudzill; Hamdani, Hamdani (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research is intended to investigate the interaction between Islam and local culture as reflected in the process of acculturation displayed in the tradition of Maccera Tasi. Using an anthropological approach, this research identifies the meanings and functions of coastal community rituals as a cultural system representing maritime Islamic culture in Eastern Indonesia. Relying on Talal Asad’s theory of discursive Islam, this research argues that the interaction of Islam within maritime culture does not merely reflect a static relationship but rather demonstrates dynamic complexities. Coastal communities in Eastern Indonesia, on the one hand, cooperatively preserve local traditions as cultural identity, while on the other hand, some groups resist by abandoning established traditions. By employing a qualitative method with data collection techniques such as in-depth interviews, documentation, archives, and digital sources, this research finds that the Maccera Tasi tradition reflects the adaptation of Islam within historical and cultural frameworks through various manifestations, such as the reinforcement of Islamic principles, the adoption of the adhan in four directions as the opening of the ritual, the transformation of the buffalo head offering into fish feed, and the practice of monotheistic prayers for safety. These findings broaden the understanding of the interaction between Islam and maritime culture, affirming that Islamic values are not only transformed but also embodied contextually within the symbolic, social and ecological spheres of coastal communities. This research provides an important contribution to understanding the dynamics of Islamic acculturation in the maritime regions of Southeast Asia. الملخص تهدف هذه الدراسة إلى دراسة التفاعل بين الإسلام والثقافة المحلية كما تتجلى في عملية التثاقف التي تتجلى في تراث ماشيرا تاسي. وباستخدام نهج أنثروبولوجي، تُحدد هذه الدراسة معنى ووظيفة طقوس المجتمعات الساحلية كنظام ثقافي يُمثل الثقافة الإسلامية البحرية في شرق إندونيسيا. واستنادًا إلى نظرية طلال أسد الخطابية الإسلامية، تُجادل هذه الدراسة بأن تفاعل الإسلام والثقافة البحرية لا يعكس علاقة ثابتة فحسب، بل يُظهر تعقيدًا ديناميكيًا. فمن جهة، تُحافظ المجتمعات الساحلية في شرق إندونيسيا بشكل تعاوني على التقاليد المحلية كهويات ثقافية، بينما تُقاومها بعض الجماعات بالتخلي عن التقاليد الراسخة. باستخدام الأساليب النوعية وتقنيات جمع البيانات مثل المقابلات المتعمقة والتوثيق والأرشيفات والمصادر الرقمية، تجد هذه الدراسة أن تقليد ماسيرا تاسي يعكس تكيف الإسلام في إطار تاريخي وثقافي من خلال مظاهر مختلفة، مثل تعزيز المبادئ الإسلامية، واستخدام الدعوة الرباعية للصلاة كبداية طقسية، وتحويل قرابين رأس الجاموس إلى طعام للأسماك، وممارسة الصلاة التوحيدية من أجل الخلاص .تُوسّع هذه النتائج فهمنا للتفاعل بين الإسلام والثقافة البحرية، مؤكدةً أن القيم الإسلامية لا تتحوّل فحسب، بل تتجسد أيضًا في سياقها في المجالات الرمزية والاجتماعية والبيئية للمجتمعات الساحلية. يُقدّم هذا البحث مساهمة مهمة في فهم ديناميكيات التثاقف الإسلامي في جنوب شرق آسيا البحري. Abstrak Penelitian ini bertujuan untuk mengkaji interaksi antara Islam dan budaya lokal sebagaimana tercermin dalam proses akulturasi yang ditampilkan dalam tradisi Maccera Tasi. Dengan pendekatan antropologis, penelitian ini mengidentifikasi makna dan fungsi ritual masyarakat pesisir sebagai sistem budaya yang merepresentasikan budaya Islam maritim di Indonesia Timur. Berdasarkan teori Islam diskursif Talal Asad, penelitian ini berargumen bahwa interaksi Islam dalam budaya maritim tidak sekadar mencerminkan hubungan yang statis, melainkan menunjukkan kompleksitas yang dinamis. Masyarakat pesisir di Indonesia Timur, di satu sisi, secara kooperatif melestarikan tradisi lokal sebagai identitas budaya, sementara di sisi lain, beberapa kelompok melakukan perlawanan dengan meninggalkan tradisi yang telah mapan. Dengan menggunakan metode kualitatif dan teknik pengumpulan data seperti wawancara mendalam, dokumentasi, arsip, dan sumber digital, penelitian ini menemukan bahwa tradisi Maccera Tasi mencerminkan adaptasi Islam dalam kerangka sejarah dan budaya melalui berbagai manifestasinya, seperti penguatan prinsip-prinsip Islam, penggunaan azan empat arah sebagai pembuka ritual, transformasi sesaji kepala kerbau menjadi pakan ikan, dan praktik doa tauhid untuk keselamatan. Temuan-temuan ini memperluas pemahaman tentang interaksi antara Islam dan budaya maritim, menegaskan bahwa nilai-nilai Islam tidak hanya ditransformasikan tetapi juga diwujudkan secara kontekstual dalam ranah simbolik, sosial dan ekologis masyarakat pesisir. Penelitian ini memberikan kontribusi penting untuk memahami dinamika akulturasi Islam di kawasan maritim Asia Tenggara.